CALCULATIONAL ANALYSIS AND EXPERIMENTAL RESEARCH ON STABILITY OF THE ROD OF CONCRETE-PUMP TRUCK’S BOOM SYSTEM - YUE HongXu; WU BinXing; XIE YuanMing (Jixie qiangdu)
The dynamic model of boom-system on concrete-pump was built,and the optimization analysis was done to obtain the maximum pressure of the compressed rod and the posture of boom system at the exact situation. Two methods were adopted to analyse the rod’s static and dynamic performance,which avoids the defects of single analysis method. A compression experiment was done on the rod using the Self-balance loading test bed. The experimental result tells that bias placing the rod has some effect on the stability of the rod and the stress distribution on its plate.